Resin composition and molded article
By using a core-shell elastomer with a specific range of cross-linking index and particle size in polyacetal resin, the problems of insufficient welding elongation and impact resistance in the existing technology are solved, and more excellent resin compositions and Molded product performance.
Patent Information
- Application Number
- CN202380045070.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-09
- Filing Date
- 2023-06-02
- Publication Date
- 2025-01-24
AI Technical Summary
It is difficult to obtain polyacetal resin molded products with better welding elongation and better impact resistance in the prior art.
By blending a core-shell elastomer with a cross-linking index of 0.24 to 0.30 in the polyacetal resin, the average secondary particle size is 10 to 250 nm, and the amount of potassium in the core-shell elastomer is greater than 0% by mass and 0.05% by mass. The following resin composition is used to improve the softness, weld elongation and impact resistance of the resin composition.
We have realized resin compositions and molded products with excellent softness, high weld elongation, and excellent impact resistance, meeting higher performance requirements.
Smart Images

Figure BDA0005171158340000151 
Figure BDA0005171158340000161 
Figure BDA0005171158340000171
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition and a molded product, and particularly to a resin composition containing a polyacetal resin as a main component. Background Art
[0002] Polyacetal resin is a plastic with excellent mechanical properties, electrical properties, chemical resistance and other chemical properties, and has been used in a wide range of applications.
[0003] Here, in order to make the polyacetal resin soft, the addition of an elastomer was studied.
[0004] For example, Patent Document 1 describes a resin composition comprising a polyacetal resin and a core-shell elastomer, wherein the resin composition is molded into a multi-purpose test piece having a thickness of 4 mm, and the flexural modulus measured in accordance with ISO178 is 1700 MPa or less, and the resin composition is molded into a test piece having a thickness of 1.6 mm and having a weld portion in the center, and the weld elongation when stretched at 10 mm / min in accordance with ASTM D638 is 20% or more.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2021-011562 Summary of the invention
[0008] Problems to be solved by the invention
[0009] The molded article obtained from the resin composition described in Patent Document 1 has excellent softness, excellent weld elongation and excellent impact resistance. However, with the recent technological innovation, a resin composition capable of obtaining a molded article having a better weld elongation and a better impact resistance is required.
[0010] The present invention aims to solve the above problems and provides a resin composition containing a core-shell elastomer, which has excellent flexibility, high weld elongation and excellent impact resistance, and a molded article formed from the resin composition.
[0011] Solutions to the problem
[0012] Based on the above problems, the present inventors have conducted research and found that the above problems can be solved by adding a core-shell elastomer satisfying a given crosslinking index, average secondary particle size and potassium element content to a polyacetal resin.
[0013] Specifically, the above problems can be solved by the following methods.
[0014] <1> A resin composition comprising a polyacetal resin (A) and a core-shell elastomer (B),
[0015] The crosslinking index of the core-shell elastomer (B) is in the range of 0.24 to 0.30.
[0016] In the polyacetal resin (A), the average secondary particle size of the core-shell elastomer (B) is 10 to 250 nm.
[0017] The amount of potassium element in the core-shell elastomer (B) is greater than 0 mass % and not more than 0.05 mass %.
[0018] <2> The resin composition according to <1>, wherein
[0019] The melt volume flow rate (MVR) of the polyacetal resin (A) measured under the conditions of temperature 190°C and load 2.16 kg according to ISO1133 is 0.5 to 20 cm 3 / 10 points.
[0020] <3> The resin composition according to <1> or <2>, wherein
[0021] The content of the core-shell elastomer (B) in the resin composition is 5 to 40% by mass.
[0022] <4> The resin composition according to any one of <1> to <3>, wherein
[0023] The content of the butadiene unit in the core-shell elastomer (B) is 50 to 80% by mass.
[0024] <5> The resin composition according to any one of <1> to <4>, wherein
[0025] In the above core-shell elastomer (B), the core comprises a butadiene-containing rubber, and the shell comprises an acrylic resin.
[0026] <6> The resin composition according to any one of <1> to <5>, wherein
[0027] The core-shell elastomer (B) contains styrene units.
[0028] <7> The resin composition according to any one of <1> to <6>, wherein
[0029] The content of styrene units in the core-shell elastomer (B) is greater than 0% by mass and not more than 5% by mass.
[0030] <8> The resin composition according to any one of <1> to <7>, wherein
[0031] The amount of polyurethane contained in the resin composition is 0 to 1% by mass.
[0032] <9> The resin composition according to any one of <1> to <8>, comprising a polyacetal resin (A) and a core-shell elastomer (B),
[0033] The crosslinking index of the core-shell elastomer (B) is in the range of 0.24 to 0.30.
[0034] In the polyacetal resin (A), the average secondary particle size of the core-shell elastomer (B) is 10 to 250 nm.
[0035] The amount of potassium in the core-shell elastomer (B) is greater than 0% by mass and less than 0.05% by mass,
[0036] The melt volume flow rate (MVR) of the polyacetal resin (A) measured under the conditions of temperature 190°C and load 2.16 kg according to ISO1133 is 0.5 to 20 cm 3 / 10 points,
[0037] The content of the core-shell elastomer (B) in the resin composition is 5 to 40% by mass.
[0038] The content of butadiene units in the core-shell elastomer (B) is 50 to 80% by mass.
[0039] In the core-shell elastomer (B), the core comprises a butadiene-containing rubber, the shell comprises an acrylic resin,
[0040] The core-shell elastomer (B) comprises styrene units, and the content of the styrene units in the core-shell elastomer (B) is greater than 0% by mass and less than 5% by mass,
[0041] The amount of polyurethane contained in the resin composition is 0 to 1% by mass.
[0042] <10> Pellets comprising the resin composition according to any one of <1> to <9>.
[0043] <11> A molded article formed from the resin composition according to any one of <1> to <9>.
[0044] <12> A molded article formed from the pellets according to <10>.
[0045] Effects of the Invention
[0046] According to the present invention, a resin composition having high weld elongation and excellent impact resistance and a molded article formed from the resin composition can be provided, in which a core-shell elastomer is blended and the resin composition has excellent flexibility. DETAILED DESCRIPTION
[0047] Hereinafter, a mode for implementing the present invention (hereinafter, simply referred to as "this embodiment") will be described in detail. It should be noted that the following this embodiment is an example for describing the present invention, and the present invention is not limited to this embodiment.
[0048] In addition, in this specification, "to" is used to mean that the numerical values described before and after it are included as a lower limit and an upper limit.
[0049] In this specification, various physical property values and characteristic values are values at 23°C unless otherwise specified.
[0050] The measurement methods and the like described in the standards shown in this specification may differ depending on the year, but unless otherwise specified, they are based on the standards as of January 1, 2022.
[0051] The resin composition of the present embodiment comprises a polyacetal resin (A) and a core-shell elastomer (B), wherein the crosslinking index of the core-shell elastomer (B) is in the range of 0.24 to 0.30, the average secondary particle size of the core-shell elastomer (B) in the polyacetal resin (A) is in the range of 10 to 250 nm, and the amount of potassium element in the core-shell elastomer (B) is greater than 0% by mass and is not more than 0.05% by mass.
[0052] By setting it as such a structure, the resin composition which is excellent in flexibility, high in weld elongation, and excellent in impact resistance can be obtained.
[0053] <Polyacetal resin (A)>
[0054] The resin composition of the present embodiment contains a polyacetal resin (A).
[0055] The polyacetal resin (A) is not particularly limited and may be a homopolymer containing only a divalent oxymethylene group as a structural unit, or a copolymer containing a divalent oxymethylene group and a divalent oxyalkylene group having 2 to 6 carbon atoms as structural units.
[0056] Examples of the oxyalkylene group having 2 to 6 carbon atoms include oxyethylene, oxypropylene, and oxybutylene.
[0057] In the polyacetal resin, the ratio of the oxyalkylene group having 2 to 6 carbon atoms to the total molar number of the oxymethylene group and the oxyalkylene group having 2 to 6 carbon atoms is not particularly limited and may be 0.5 to 10 mol %.
[0058] In order to produce the polyacetal resin (A), three In order to introduce an oxyalkylene group having 2 to 6 carbon atoms into the polyacetal resin, a cyclic formal or a cyclic ether can be used. Specific examples of cyclic formals include 1,3-dioxolane, 1,3-dioxolane, Examples of the cyclic ethers include 1,3-dioxolane, 1,3-dioxolane, 1,3,5-trioxolane, 1,3,6-trioxolane, and the like. Specific examples of the cyclic ethers include ethylene oxide, propylene oxide, and butylene oxide. To introduce ethylene oxide into the polyacetal resin (A), 1,3-dioxolane may be used as the main raw material. To introduce propylene oxide, 1,3-dioxolane may be used as the main raw material. In order to introduce oxybutylene groups, 1,3-dioxepane can be used as the main raw material. It should be noted that in the polyacetal resin, the amount of hemiformal terminal groups, formyl terminal groups, and terminal groups unstable to heat, acid, and alkali are preferably small. Here, the hemiformal terminal group refers to the terminal group with -OCH 2 The group represented by OH and the formyl terminal group refer to the group represented by -CHO.
[0059] The polyacetal resin (A) used in the present embodiment preferably has a melt volume flow rate (MVR) of 0.5 cm / s as measured under the conditions of a temperature of 190° C. and a load of 2.16 kg according to ISO 1133. 3 / 10 minutes or more, more preferably 0.6 cm 3 / 10 minutes or more, more preferably 0.8 cm 3 / 10 minutes or more, more preferably 1cm 3 / 10 minutes or more, more preferably 5cm 3 / 10 minutes or more. By setting it to be more than the above lower limit, there is a tendency that the productivity of the resin composition is further improved. In addition, the MVR of the above polyacetal resin (A) is, for example, 30 cm 3 / 10 minutes or less, preferably 20cm 3 / 10 minutes or less, more preferably 18cm 3 / 10 minutes or less, more preferably 14cm 3 / 10 minutes or less, more preferably 10cm 3 / 10 minutes or less, and more preferably 8 cm 3 By setting it below the said upper limit, the dispersibility of a core-shell elastomer (B) will improve, and there exists a tendency to be able to reduce the average secondary particle diameter of a core-shell elastomer (B).
[0060] As the polyacetal resin, in addition to the above, the polyacetal resins described in paragraphs 0018 to 0043 of JP-A-2015-074724 may be used, and the contents thereof are incorporated herein.
[0061] The resin composition of the present embodiment preferably comprises more than 60% by mass of (A) polyacetal resin, more preferably more than 70% by mass, further preferably more than 72% by mass, and may be more than 76% by mass. The upper limit is preferably less than 95% by mass, more preferably less than 90% by mass, and further preferably less than 85% by mass. By being set to such a scope, there is a tendency to more effectively exert the effect of the present embodiment.
[0062] The resin composition of the present embodiment may contain only one polyacetal resin or two or more polyacetal resins. When containing two or more polyacetal resins, the total amount is preferably within the above range.
[0063] <Core-shell elastomer (B)>
[0064] The resin composition of the present embodiment includes a core-shell elastomer (B). The core-shell elastomer is a polymer having a multilayer structure having a core and a shell layer covering part or all of the core, and known ones include Kane Ace series from Kaneka Co., Ltd. and Metablen series from Mitsubishi Chemical Corporation.
[0065] The crosslinking index of the core-shell elastomer (B) used in this embodiment is in the range of 0.24 to 0.30, the average secondary particle size in the polyacetal resin (A) is 10 to 250 nm, and the amount of potassium is greater than 0% by mass and less than 0.05% by mass. By setting such a structure, a molded product with high weld elongation and excellent impact resistance can be obtained.
[0066] The crosslinking index of the core-shell elastomer (B) is in the range of 0.24 to 0.30, preferably 0.25 or more, preferably 0.29 or less, more preferably 0.28 or less, and further preferably 0.27 or less. The crosslinking index refers to the degree of intermolecular crosslinking of the core portion of the core-shell elastomer. That is, the larger the crosslinking index, the harder the elastomer is, and the smaller the crosslinking index, the softer the elastomer is. By setting the crosslinking index to above the above lower limit, the weld elongation increases. It can be inferred that this is because the harder the elastomer is, the less it will deform due to the force applied to the weld during molding, and the more it can maintain its spherical shape. In addition, by setting the crosslinking index to below the above upper limit, there is a tendency for the impact resistance of the resin composition to be further improved.
[0067] The crosslinking index of the core-shell elastomer (B) can be adjusted according to the polymerization conditions when the core-shell elastomer is produced.
[0068] The crosslinking index of the core-shell elastomer (B) can be calculated from the results of measurement as described in the Examples described below.
[0069] The average secondary particle size of the core-shell elastomer (B) is 10 to 250 nm in the polyacetal resin (A). The average secondary particle size of the core-shell elastomer (B) in the present embodiment is the secondary average particle size in the molded product. By setting the average secondary particle size of the core-shell elastomer (B) to less than 250 nm, the core-shell elastomer (B) is easily dispersed in the polyacetal resin (A), the weld elongation can be improved, and the impact resistance can be improved. This is because if the average secondary particle size of the core-shell elastomer (B) increases, the core-shell elastomer (B) will become the starting point of destruction in the molded product. In addition, the force applied to the interface between the core-shell elastomer (B) and the polyacetal resin (A) is also reduced, which can improve the weld elongation and improve the impact resistance. The secondary average particle size of the core-shell elastomer (B) in such a polyacetal resin (A) can be achieved by adjusting the selection of the type of the core-shell elastomer (B), the fluidity of the polyacetal resin, the conditions of melt kneading, etc.
[0070] The average secondary particle size of the core-shell elastomer (B) is preferably 240 nm or less, more preferably 210 nm or less, further preferably 180 nm or less, further preferably 150 nm or less, and further preferably 120 nm or less. In addition, the average secondary particle size of the core-shell elastomer (B) is preferably 20 nm or more, more preferably 30 nm or more, further preferably 50 nm or more, further preferably 80 nm or more, and further preferably 100 nm or more.
[0071] The average secondary particle size of the core-shell elastomer (B) can be measured according to the description in the Examples described below.
[0072] The amount of potassium in the core-shell elastomer (B) is greater than 0% by mass and is less than 0.05% by mass. By setting it below the above upper limit, it is possible to effectively suppress the potassium element from becoming a source and generating a starting point for damage in the molded product. By setting it above the above lower limit, there is a tendency to suppress the decomposition of the resin when added to the polyacetal resin. The amount of potassium in the core-shell elastomer (B) is preferably less than 0.04% by mass, more preferably less than 0.03% by mass, and is preferably more than 0.01% by mass, and further preferably greater than 0.01% by mass. In the present embodiment, the detection limit is set to 0% by mass.
[0073] The potassium element in the core-shell elastomer (B) may be contained in the form of a potassium-containing compound, or in the form of potassium ions or potassium element alone.
[0074] The amount of potassium element in the core-shell elastomer (B) can be obtained by, for example, washing a commercially available core-shell elastomer.
[0075] The amount of potassium element can be measured according to the description in the examples described below.
[0076] The type of core-shell elastomer used in this embodiment is not particularly limited, and the core is preferably a rubber polymer. As the rubber polymer, it is preferred to include at least one selected from butadiene-containing rubber, butyl acrylate-containing rubber, 2-ethylhexyl acrylate-containing rubber, and silicone rubber, and more preferably includes butadiene-containing rubber.
[0077] The core-shell elastomer used in the present embodiment preferably contains a styrene unit. The inclusion of a styrene unit tends to improve the impact resistance of the resulting molded article.
[0078] In the core-shell elastomer used in the present embodiment, the content of butadiene units is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 65% by mass or more, further preferably 70% by mass or more, and preferably 80% by mass or less.
[0079] In addition, when the core-shell elastomer used in the present embodiment contains a styrene unit, the content thereof is preferably greater than 0 mass%, more preferably 0.5 mass% or more, and is preferably 5 mass% or less, more preferably 3 mass% or less, and further preferably 2 mass% or less.
[0080] In the core-shell elastomer used in the present embodiment, the total content of butadiene units, styrene units, and (meth)acrylate units (preferably methyl methacrylate) is preferably 98% by mass or more.
[0081] The shell of the core-shell elastomer used in this embodiment is preferably a polymer of one or more monomers selected from (meth)acrylates (preferably methyl methacrylate), aromatic vinyl compounds, etc., and more preferably a polymer (acrylic resin) in which units derived from (meth)acrylates (preferably methyl methacrylate) account for more than 50% by mass of the total.
[0082] In the core-shell elastomer used in the present embodiment, it is preferred that the core contains a rubber-based polymer and the shell contains an acrylic resin. If such a core-shell elastomer is used, there is a tendency that the effects of the present invention can be more effectively exerted.
[0083] The resin composition of the present embodiment preferably contains more than 5% by mass of the core-shell elastomer (B), more preferably more than 10% by mass, and further preferably more than 15% by mass. By setting it to more than the above lower limit, there is a tendency that the impact resistance is further improved. The upper limit is preferably less than 40% by mass, more preferably less than 30% by mass, and further preferably less than 28% by mass, and can also be less than 24% by mass. By setting it to less than the above upper limit, there is a tendency that the impact resistance is further improved.
[0084] The resin composition of the present embodiment may contain only one core-shell elastomer or two or more thereof. When containing two or more thereof, the total amount is preferably within the above range.
[0085] In the resin composition of the present embodiment, the total amount of the polyacetal resin (A) and the core-shell elastomer (B) preferably accounts for 95% by mass or more of the resin composition, and more preferably accounts for 98% by mass or more. However, the total amount of the polyacetal resin (A) and the core-shell elastomer (B) does not exceed 100% by mass.
[0086] <Other ingredients>
[0087] The resin composition of the present embodiment may include any known additives and fillers within the scope of not damaging the purpose of the present invention. As additives and fillers used in the present embodiment, for example, thermoplastic resins other than polyacetal resins, ultraviolet absorbers, antioxidants, stabilizers, formaldehyde scavengers, antistatic agents, carbon fibers, glass fibers, glass flakes, potassium titanate whiskers, etc. can be cited. Their details can be referred to the records of paragraphs 0113 to 0124 of Japanese Patent Publication No. 2017-025257, and their contents are introduced into this specification.
[0088] The resin composition of the present embodiment preferably does not substantially contain polyurethane. Substantially free means that the amount of polyurethane contained in the resin composition is 0 to 1% by mass, preferably 0 to 0.5% by mass, more preferably 0 to 0.1% by mass, and may also be 0% by mass. By reducing the content of polyurethane, the weld elongation of the obtained molded product can be further improved.
[0089] <Physical properties of resin composition>
[0090] The resin composition of the present embodiment preferably has excellent weld elongation. Specifically, the resin composition of the present embodiment is molded into an ASTM tensile test piece (thickness 1.6 mm), and the weld elongation during the tensile test according to ASTM D638 is preferably 95% or more, preferably 98% or more, and more preferably 100% or more. In addition, the upper limit of the above-mentioned weld elongation is, for example, 300% or less.
[0091] The resin composition of the present embodiment preferably has excellent impact resistance. Specifically, according to ISO179-1, the Charpy impact strength of a test piece having a length of 80 mm, a width of 10 mm, a thickness of 4 mm, and a notch with a tip radius of r = 0.25 mm is preferably 20 kJ / m 2 More preferably, 21 kJ / m 2 There is no particular upper limit, but it is 50 kJ / m 2 the following.
[0092] The weld elongation and Charpy impact strength can be measured according to the description in the examples described later.
[0093] <Method for producing resin composition>
[0094] The resin composition of the present embodiment contains the above-mentioned essential components and the above-mentioned optional components used as needed. Moreover, the manufacturing method thereof can select any method so that the average secondary particle size reaches the above-mentioned range. The manufacturing method of any resin composition known in the art can be used to mix / knead these raw materials.
[0095] As one of the methods for making the average secondary particle size within the above range, there can be cited a method in which a polyacetal resin and a core-shell elastomer are mixed with a roller, extruded through a melt-kneading machine, and cut into strands to form particles. At this time, as a melt-kneading machine, a twin-screw extruder is preferably used from the aspect that secondary coagulation is easy to occur in the case of a single-screw extruder. Among them, the ratio of the length L (mm) of the screw to the diameter D (mm) of the screw, i.e., L / D, is preferably 20 or more, more preferably 30 or more, and preferably 100 or less, more preferably 70 or less. By setting the above L / D to 20 or more, the core-shell elastomer is easily micro-dispersed, and the secondary coagulation of the core-shell elastomer can be effectively suppressed. In addition, by setting the above L / D to 100 or less, there is a tendency to effectively suppress the discoloration of the resin composition caused by thermal degradation.
[0096] The shape of the die nozzle is not particularly limited. From the perspective of particle shape, a circular nozzle with a diameter of 1 mm or more is preferred, and a circular nozzle with a diameter of 2 mm or more is more preferred. A circular nozzle with a diameter of 10 mm or less is also preferred, and a circular nozzle with a diameter of 7 mm or less is more preferred.
[0097] In addition, the melting temperature of the resin composition during melt kneading is preferably 170° C. or higher, more preferably 190° C. or higher, and preferably 250° C. or lower, more preferably 230° C. or lower. By setting the melting temperature to 170° C. or higher, there is a tendency that melting becomes sufficient and production volume is improved. In addition, by setting it to 250° C. or lower, there is a tendency that discoloration of the resin composition caused by thermal degradation can be effectively suppressed.
[0098] The screw structure of the twin-screw extruder is not particularly limited, and one of the preferred embodiments is to have at least two kneading sections. The kneading section has a kneading disk, which mainly contributes to the melting of the resin and the dispersion of the elastomer.
[0099] The screw speed during melt kneading is preferably 50 rpm or more, more preferably 70 rpm or more, further preferably 80 rpm or more, and preferably 500 rpm or less, more preferably 350 rpm or less. By setting the screw speed to 50 rpm or less, the core-shell elastomer is easily micro-dispersed, and there is a tendency to more effectively suppress the occurrence of secondary agglomeration. In addition, by setting it to 500 rpm or less, the heat generated during melt kneading can be suppressed, and there is a tendency to effectively suppress the discoloration of the resin composition caused by thermal degradation. In addition, the ejection amount is preferably 5 kg / hr or more, more preferably 7 kg / hr or more, and preferably 1000 kg / hr or less, more preferably 800 kg / hr or less. By setting it to 5 kg / hr or more, the core-shell elastomer is more easily micro-dispersed, and the occurrence of secondary agglomeration can be effectively suppressed. In addition, by setting it to 1000 kg / hr or less, the heat generated during melt kneading can be effectively suppressed, and there is a tendency to effectively suppress the discoloration of the resin composition caused by thermal degradation.
[0100] The ratio (Q / Ns) of the screw speed (Ns) to the discharge amount (Q) during melt kneading also depends on the screw diameter and screw structure of the extruder, and is, for example, preferably 0.5 or more, more preferably 0.7 or more, particularly preferably 0.9 or more, and preferably 1.5 or less, more preferably 1.3 or less, particularly preferably 1.2 or less. The above Q / Ns is particularly preferred in an embodiment in which the screw diameter is 18 to 75 mm (further 58 mm) and has two kneading sections as the screw structure.
[0101] Examples of the mixer include a kneader, a Banbury mixer, an extruder, etc. There are no particular restrictions on the various conditions and devices for mixing / kneading, and they can be appropriately selected and determined from any known conditions. Kneading is preferably carried out at a temperature above the melting temperature of the polyacetal resin, specifically above the melting temperature of the polyacetal resin (generally above 180° C.).
[0102] <Molding products>
[0103] The molded article of the present embodiment is formed from the resin composition of the present embodiment. The resin composition of the present embodiment is usually injection molded as it is or by pelletizing the pellets to produce a molded article.
[0104] That is, a preferred example of the molded product of the present embodiment is an injection molded product. An injection molded product is a molded product obtained by injection molding, and generally, a weak portion (weld portion) is formed at a portion where molten resins merge in a mold.
[0105] The shape of the molded product is not particularly limited and can be appropriately selected according to the use and purpose of the molded product, and examples thereof include: plate-shaped, disk-shaped, rod-shaped, sheet-shaped, film-shaped, cylindrical, ring-shaped, circular, elliptical, gear-shaped, polygonal, special-shaped, hollow, frame-shaped, box-shaped, panel-shaped, cap-shaped, etc. The molded product of the present invention can be a component or a finished product.
[0106] <Application>
[0107] The resin composition of the present embodiment and the molded article formed from the resin composition can be exemplified by automobile parts such as trim clips, seat belt components, and headrest rails, building material parts, electrical / electronic parts, commercial equipment parts, daily sundry parts, and containers for frozen foods, beverages, etc., household appliances such as refrigerator gaskets, hose clamps, packaging, and strapping tapes.
[0108] Example
[0109] Below, give embodiment and the present invention is described more specifically.As long as do not depart from the gist of the present invention, the material, dosage, ratio, processing content, processing steps etc. shown in the following embodiment can be appropriately changed.Therefore, the scope of the present invention is not limited to the specific example shown below.
[0110] When the measuring equipment used in the examples is difficult to obtain due to discontinuation of production or the like, other equipment having equivalent performance may be used for measurement.
[0111] 1. Raw materials
[0112] The raw materials shown in the following Table 1-1 were used.
[0113] [Table 1-1]
[0114] Abbreviation Details F20-03 <![CDATA[Polyoxymethylene resin, MVR: 7.7 cm 3 / 10 min, manufactured by Mitsubishi Engineering-Plastics Corporation]]> F10-EW <![CDATA[Polyoxymethylene resin, MVR: 3.4 cm 3 / 10 min, manufactured by Mitsubishi Engineering-Plastics Corporation]]> A10-03 <![CDATA[Polyoxymethylene resin, MVR: 2.2 cm 3 / 10 min, manufactured by Mitsubishi Engineering-Plastics Corporation]]> F30-03 <![CDATA[Polyoxymethylene resin, MVR: 23 cm 3 / 10 min, manufactured by Mitsubishi Engineering-Plastics Corporation]]> M-910 Kane Ace M-910, manufactured by Kaneka Co., Ltd., core-shell elastomer EXL-2600 PARALOID EXL-2600, manufactured by Dow Chemical, core-shell elastomer E-860A Metablen E-860, Mitsubishi Chemical Corporation, Core-shell elastomer M-732 Kane Ace M-732, manufactured by Kaneka Co., Ltd., core-shell elastomer
[0115] The above MVR is the melt volume flow rate measured under the conditions of a temperature of 190° C. and a load of 2.16 kg according to ISO1133.
[0116] <Analysis of the composition of the elastomer>
[0117] The composition of each core-shell elastomer (composition of the core and shell combined) was analyzed as follows. Based on the amount of each element obtained by organic element analysis, the abundance ratio of each constituent component of the core-shell elastomer obtained by thermal decomposition GC / MS analysis was calculated as the composition ratio. Thermal decomposition GC / MS measurement was performed. The device configuration and conditions of thermal decomposition GC / MS are as follows.
[0118] Device composition
[0119] Furnace: EGA / PY-3030D manufactured by Frontier Laboratories
[0120] GC: GC-2030 manufactured by Shimadzu Corporation
[0121] MS: GCMS-QP2020 NX
[0122] Conditions
[0123] Pyrolyzer 600℃
[0124] Column: UA-5, 0.25 mm I.D. × 30 m × 0.25 μm
[0125] Temperature conditions:
[0126] Flow: 1.0 mL / min.
[0127] Split: 1∶30
[0128] Inj / IF: 200℃ / 300℃
[0129] The apparatus and measurement mode for organic elemental analysis are as described below.
[0130] Apparatus: vario EL cube manufactured by Elementar
[0131] Measurement mode: CHN mode and O mode
[0132] The unit is mass%.
[0133] The results are shown in Table 1-2 below.
[0134] [Table 1-2]
[0135] M-910 EXL-2600 E-860A M-732 MMA (methyl methacrylate) 22 25 24 24 BA(Benzyl Acrylate) 1 ND ND ND Bd (butadiene) 76 74 71 69 St(Styrene) 1 1 5 7
[0136] <Preparation of the cleaning products of M-910>
[0137] The cleaning products A to C of M-910 shown in Tables 2 to 6 were prepared as described below.
[0138] 100 parts by mass of M910 was put into 200 parts by mass of pure water, stirred for 10 minutes by a stirrer, and then solid-liquid separation was carried out by suction filtration. The operation was repeated 5 times for cleaning product A, 3 times for cleaning product B, and 1 time for cleaning product C. The solids obtained by the above operation were dried by a vacuum dryer at 60℃ and used as samples in the examples.
[0139] <Amount of potassium element in the core-shell elastomer>
[0140] The amount of potassium element in the core-shell elastomer used in each of the examples and comparative examples was measured using "ZSXminiII" manufactured by RIGAKU Corporation.
[0141] The unit is expressed in mass %.
[0142] ND means below the detection limit.
[0143] <Core-shell elastomer crosslinking index>
[0144] Each core-shell elastomer used in each example and comparative example was subjected to T measurement using Minispec 20 manufactured by Bruker. 2 The relaxation time was measured at -40°C, 0°C, 23°C, and 80°C, and the T 2 The relaxation time is shown in Figure 2. The X-axis is the measurement temperature and the T 2 The approximate straight line of the curve obtained when the relaxation time is used as the Y axis can be considered that the larger the slope, the higher the molecular mobility, that is, the fewer cross-linked structures that restrict the movement of the molecules, and the smaller the slope, the lower the molecular mobility, that is, the more cross-linked structures that restrict the movement of the molecules. The reciprocal of the slope of the above approximate straight line is taken as the cross-linking index. The measurement temperatures of -40°C and 0°C were assumed by the solid echo method, and the measurement temperatures of 23°C and 80°C were measured by the spin echo method.
[0145] T 2 The relaxation time was measured under the following conditions.
[0146] Observation frequency: 25MHz
[0147] Measurement method: Solid echo method / Spin echo method
[0148] Repeat time: 4sec / 4sec
[0149] Number of points: 16 times / 4 times
[0150] Measuring temperature: -40℃, 0℃ / 23℃, 80℃
[0151] 2. Examples 1 to 9, Comparative Examples 1 to 6
[0152] <Production of resin composition (pellets)>
[0153] Using a super mixer manufactured by Kawada Manufacturing Co., Ltd., the components shown in Tables 2 to 6 were uniformly mixed in the ratios (parts by mass) shown in Tables 2 to 6. The obtained mixture was melt-shear mixed using a twin-screw extruder with a screw diameter of 30 mm, a screw length of 760, and a die nozzle diameter of 3.5 mm ("PCM-30" manufactured by Ikegai Co., Ltd.) at a barrel temperature of 200° C., a screw speed of 120 rpm, and a discharge amount of 10 kg / hour to produce pellets of the resin composition.
[0154] <Average secondary particle size of core-shell elastomer (nm)>
[0155] The pellets obtained above were heat-treated in a hot air circulation dryer at a temperature of 80° C. for 4 hours.
[0156] Next, an ASTM tensile test piece (thickness 3.2 mm) having a weld portion in the center was prepared using an injection molding machine with the barrel temperature set to 195°C and the mold temperature set to 90°C. A tensile test was performed according to ASTM D638, and the weld elongation was measured.
[0157] A test piece for observation under a scanning electron microscope (SEM) was cut out from the ASTM tensile test piece using a diamond knife in parallel with the flow direction during molding and including the welded portion.
[0158] After osmium tetroxide was vapor-deposited on the observation surface of the obtained test piece for SEM observation, a SEM image was obtained using a scanning electron microscope (SEM).
[0159] Based on the obtained SEM images, the average value of the maximum lengths of the island-like portions derived from the elastomer was taken as the average secondary particle size of the elastomer.
[0160] The injection molding machine used was EC-100S manufactured by Shibaura Corporation.
[0161] Osmium tetroxide was deposited using an "Osmium Coater" manufactured by MEIWAFOSIS at 8 mA for 60 seconds. Scanning electron microscopy was performed using a "Scanning Electron Microscope (SEM) S-4800" manufactured by Hitachi High-Tech at an acceleration voltage of 1 kV, a signal of LA100 (U), an emission current of 6 μA, and a detection current of Normal to obtain SEM images.
[0162] <Welding elongation>
[0163] The pellets obtained above were heat treated in a hot air circulation dryer at a temperature of 80° C. for 4 hours.
[0164] Next, an ASTM tensile test piece (thickness 1.6 mm) having a weld portion in the center was prepared using an injection molding machine with the barrel temperature set to 195°C and the mold temperature set to 90°C. A tensile test was performed according to ASTM D638, and the weld elongation was measured.
[0165] The injection molding machine used was EC-100S manufactured by Shibaura Machine Co., Ltd.
[0166] The results are shown in the following Tables 2 to 6. The unit is %.
[0167] <Notched Charpy impact strength (kJ / m 2 )>
[0168] The pellets obtained above were heat treated in a hot air circulation dryer at a temperature of 80° C. for 4 hours.
[0169] Next, the dried pellets were formed into 4 mm thick multi-purpose test pieces at a mold temperature of 80°C and a barrel temperature of 190°C. Then, in accordance with ISO179-1, a grooving tool manufactured by Toyo Seiki Co., Ltd. was used to cut out test pieces of 80 mm in length × 10 mm in width × 4 mm in thickness, and a notch process with a front end radius of r = 0.25 mm was performed.
[0170] The results are shown in Tables 2 to 6. The unit is kJ / m 2 express.
[0171] [Table 2]
[0172]
[0173] [Table 3]
[0174]
[0175] [Table 4]
[0176]
[0177] [Table 5]
[0178]
[0179] [Table 6]
[0180]
[0181] From the above results, it is clear that the resin composition of the present embodiment has high weld elongation and excellent impact resistance (Examples 1 to 9).
[0182] In contrast, when the crosslinking index of the core-shell elastomer (B) is out of the range of 0.24 to 0.30 (Comparative Example 2), or when the crosslinking index satisfies the range of 0.24 to 0.30 but the average secondary particle size is greater than 250 nm (Comparative Example 3), the weld elongation is low. In addition, in the comparative examples with slightly higher crosslinking indexes, although the weld elongation is slightly higher, the Charpy impact strength is poor (Comparative Example 1).
[0183] In addition, even if the crosslinking index and the average secondary particle size of the core-shell elastomer (B) are within the range of the present invention, when the amount of potassium in the core-shell elastomer (B) is outside the range of more than 0 mass % and 0.05 mass % or less (Comparative Example 4), the weld elongation is low. In particular, as can be seen from the comparison between Example 3 and Comparative Example 4, a significant difference in weld elongation is observed when the amount of potassium in the core-shell elastomer (B) is 0.05 mass %.
[0184] On the other hand, even though the crosslinking index and potassium element content of the core-shell elastomer (B) were within the ranges of the present invention, when the average secondary particle size of the core-shell elastomer (B) was outside the ranges of the present invention (Comparative Example 5), the weld elongation and Charpy impact strength were inferior.
Claims
1. A resin composition comprising a polyacetal resin (A) and a core-shell elastomer (B), The crosslinking index of the core-shell elastomer (B) is in the range of 0.24 to 0.30, In the polyacetal resin (A), the average secondary particle size of the core-shell elastomer (B) is 10 to 250 nm. The amount of potassium element in the core-shell elastomer (B) is greater than 0 mass % and is 0.05 mass % or less.
2. The resin composition according to claim 1, wherein The melt volume flow rate (MVR) of the polyacetal resin (A) measured under the conditions of temperature 190°C and load 2.16 kg according to ISO1133 is 0.5 to 20 cm 3 / 10 points.
3. The resin composition according to claim 1 or 2, wherein The content of the core-shell elastomer (B) in the resin composition is 5 to 40% by mass.
4. The resin composition according to claim 1 or 2, wherein The content of butadiene units in the core-shell elastomer (B) is 50 to 80% by mass.
5. The resin composition according to claim 1 or 2, wherein In the core-shell elastomer (B), the core comprises a butadiene-containing rubber, and the shell comprises an acrylic resin.
6. The resin composition according to claim 1 or 2, wherein The core-shell elastomer (B) comprises styrene units.
7. The resin composition according to claim 1 or 2, wherein The content of styrene units in the core-shell elastomer (B) is greater than 0% by mass and not more than 5% by mass.
8. The resin composition according to claim 1 or 2, wherein The amount of polyurethane contained in the resin composition is 0 to 1% by mass.
9. The resin composition according to claim 1, comprising a polyacetal resin (A) and a core-shell elastomer (B), The crosslinking index of the core-shell elastomer (B) is in the range of 0.24 to 0.30, In the polyacetal resin (A), the average secondary particle size of the core-shell elastomer (B) is 10 to 250 nm. The amount of potassium in the core-shell elastomer (B) is greater than 0% by mass and less than 0.05% by mass, The melt volume flow rate (MVR) of the polyacetal resin (A) measured under the conditions of temperature 190°C and load 2.16 kg according to ISO1133 is 0.5 to 20 cm 3 / 10 points, The content of the core-shell elastomer (B) in the resin composition is 5 to 40% by mass. The content of butadiene units in the core-shell elastomer (B) is 50 to 80% by mass. In the core-shell elastomer (B), the core comprises a butadiene-containing rubber, the shell comprises an acrylic resin, The core-shell elastomer (B) comprises styrene units, and the content of the styrene units in the core-shell elastomer (B) is greater than 0% by mass and less than 5% by mass, The amount of polyurethane contained in the resin composition is 0 to 1% by mass. 10 . Particles, which are particles of the resin composition according to claim 1 , 2 or 9 .
11. A molded article formed from the resin composition according to claim 1, 2 or 9.
12. A molded article formed from the pellets according to claim 10.
Citation Information
Patent Citations
Automobile interior part
JP2015074724A
Polyacetal resin composition and polyacetal resin molded article
JP2017025257A
Resin composition and molded article
JP2021011562A